HUBUNGAN ANEMIA DAN RIWAYAT PERDARAHAN POST PARTUM DENGAN TERJADINYA PERDARAHAN POST PARTUM DI BPM ENDAH KECAMATAN WAGIR KABUPATEN MALANG - Roni Subrata (Universitas Tribhuwana Tunggadewi Malang, 2022)
Neonatorial asphyxia is a condition of a newborn baby who cannot breathe spontaneously and regularly within 1 minute after birth. It usually occurs in babies born to mothers with less than one month of birth, and birth over time. In general, there are many factors that can cause asphyxia in newborns, both factors from the mother such as (elderly, poor obstetric history, grande multipara, gestation period, preeclampsia, eclampsia, anemia and maternal disease, premature rupture of the membranes, prolonged labor, narrow pelvis, intrauterine infection, fetal factors, fetal distress, multiple pregnancies, breech location, latitude, birth weight, and factors of the placenta. The purpose of this study was to determine the relationship between preeclampsia and history of hypertension with the incidence of asphyxia in infants at Ben Mari Hospital, Malang Regency. The sampling method uses accidental techniques, namely the sample used is the entire population. The data obtained are then analyzed by descriptive statistical approach. By using the method of multiple linear regression models. F-count value of 7.178 from the value of F 0.05 (3.354) means that there is a significant influence between the variables of preeclampsia (X1), and a history of hypertension (X2), with the incidence of asphyxia in infants (Y). The Rsquare is 0.465, which means the relationship of the independent variable with the incidence of asphyxia in infants is 46.5%, while the other 53.5% is influenced by other factors not examined.